For-profit hospitals as anchor institutions in the United States: a study of organizational stability - Berkeley Franz; Cory E. Cronin; Vanessa Rodriguez; Kelly Choyke; Janet E. Simon; Maxwell T. Hall (BMC, 2021)
Abstract Background Anchor institutions, by definition, have a long-term presence within their local communities, but it is uncertain as to whether for-profit hospitals meet this definition; most research on anchor institutions to date has been limited to nonprofit organizations such as hospitals and universities. Accordingly, this study aims to determine whether for-profit hospitals are stable enough to fulfill the role of anchor institutions through a long-term presence in communities which may help to stabilize local economies. Methods This longitudinal study analyzes national, secondary data between 2008 and 2017 compiled from the Dartmouth Atlas of Health Care, the American Hospital Association Annual Survey, and County Health Rankings. We use descriptive statistics to calculate the number of closures and mergers of hospitals of different ownership type, as well as staffing levels. Using logistic regression, we also assessed whether for-profit hospitals had higher odds of closing and merging, controlling for both organization and community factors. Results We found for-profit hospitals to be less stable than their public and nonprofit hospital counterparts, experiencing disproportionately more closures and mergers over time, with a multivariable analysis indicating a statistically significant difference. Furthermore, for-profit hospitals have fewer full-time employees relative to their size than hospitals of other ownership types, as well as lower total payroll expenditures. Conclusions Study findings suggest that for-profit hospitals operate more efficiently in terms of expenses, but this also may translate into a lower level of economic contributions to the surrounding community through employment and purchasing initiatives. For-profit hospitals may also not have the stability required to serve as long-standing anchor institutions. Future studies should consider whether for-profit hospitals make other types of community investments to offset these deficits and whether policy changes can be employed to encourage anchor activities from local businesses such as hospitals.